Harnessing dual applications of a novel ascomycetes yeast, Starmerella cerana sp. nov., as a biocatalyst for stereoselective ketone reduction and biosurfactant production - Kumar, Sachin; Verma, Nitish Kumar; Basotra, Sandal Deep; Sharma, Divya; Prasad, G. S.; Bhattacharyya, Mani Shankar (Frontiers in Bioengineering and Biotechnology, 2023)
In an effort to new biocatalyst for oxidation reduction reaction, novel ascomycetous yeast species of the genus Starmerella was isolated from the surface of honey bees (Apis cerana, Family Apidae). The Honey bee samples were collected at the Institute of Microbial Technology, Chandigarh, India. The sequence analysis of Internal Transcribed Spacer (ITS) and D1/D2 domains of the 26S rRNA gene sequence indicated the strain HSB-15 T was closely related to type strain of Starmerella vitae strain CBS 15147 T a member of genus Starmerella. Utilizing pair-wise alignment of ITS and D1/D2 domain sequences reveals a 96.3% and 97.7% similarity with the closely related strain, respectively. However, concatenated sequence of the ITS gene and D1/D2 domain, revealed 94.6% sequence similarity. Phenotypic characterization showed a notable difference of the strain HSB-15 T with its closely related species. The isolated culture (strain HSB-15 T ) has been deposited at Microbial Type Culture Collection and Gene Bank (MTCC, Chandigarh, India) as MTCC 12380 T = CBS 15321 T . The analysis revealed that strain HSB-15 T is a novel species different from the initially reported species, for which Starmerella cerana sp. nov., is proposed. Furthermore, we explored the potential of the strain HSB-15 T as whole-cell biocatalyst for the reduction of naphthyl ketones to their corresponding alcohols. We also observed that the novel strain is capable of producing surfactant (in its culture broth) which, upon analysis was found to be sophorolipid. Thus, HSB-15 T can serve the dual function as biocatalyst and a producer of biosurfactant.